Pengembangan Sistem Informasi Akademik Berbasis Web Menggunakan Metode Agile - Maulidin, Fazri; Saputra, Angga; Jupron, Jupro (Pustaka Galeri Mandiri, 2026)
Academic information management in schools is often still conducted manually, leading to inefficiencies, difficulties in data retrieval, and a high risk of errors. This study aims to develop a web-based academic information system to improve the effectiveness of data management. The system is developed using the Agile method, which enables iterative and flexible development based on user needs. The results indicate that the system can accelerate data processing, simplify information access, and reduce recording errors compared to the previous manual system. Therefore, the proposed system contributes to improving efficiency and supporting the digitalization of academic management in schools.